Proceedings of the 2017 ACM SIGUCCS Annual Conference 2017
DOI: 10.1145/3123458.3123459
|View full text |Cite
|
Sign up to set email alerts
|

A Touchless Gestural System for Extended Information Access Within a Campus

Abstract: the conference committee reflected on SIGUCCS conferences, what they mean to us individually, and what we hope to achieve this year. Our conference theme Connect | Discover was developed as a result of our discussions. We are confident that over the next several days, you will connect with amazing colleagues from other institutions across the US and the world, and discover new ideas and solutions to bring back to your home institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The use of touchless gestures, especially when applied to public displays, has many advantages. Among them, touchless gestural interaction limits vandalism by placing displays in unreachable places [31], keeping a high hygiene level of the screen surface [19], and removing constraints to the display size (see, for instance, works on media façades [9]). Walter et al [34] focused their work on describing existing solutions found in literature, for user representation in touchless gestural applications.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of touchless gestures, especially when applied to public displays, has many advantages. Among them, touchless gestural interaction limits vandalism by placing displays in unreachable places [31], keeping a high hygiene level of the screen surface [19], and removing constraints to the display size (see, for instance, works on media façades [9]). Walter et al [34] focused their work on describing existing solutions found in literature, for user representation in touchless gestural applications.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
“…for wheelchair users) or to avoid vandalism (e.g. by placing displays in unreachable places, still keeping their interactivity) [31]. However, one of the most common issues in this context is interaction blindness, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some displays offer implicit interaction, such as reacting to the user's natural behavior when they approach the display. This is the case of deployments where display is made more noticeable by showing silhouettes or avatars that mimic users' movements [27,33,40].…”
Section: Interaction With Pervasive Displaysmentioning
confidence: 99%
“…The use of touchless gestural interfaces have been adopted in many contexts, both in research projects and in industrial applications. They have been used in order to interact with 3D virtual objects [4], access information provision systems [12,40], create and support playful interactions [33], and many others. In the context of pervasive displays research, touchless gestural interfaces offer many advantages.…”
Section: Interaction With Pervasive Displaysmentioning
confidence: 99%
See 1 more Smart Citation